Hierarchical carbon nanofibers/graphene composite containing nanodiamonds for direct dehydrogenation of ethylbenzene. (January 2016) - Ba, Housseinou; Truong-Phuoc, Lai; Liu, Yuefeng; Duong-Viet, Cuong; Nhut, Jean-Mario; Nguyen-Dinh, Lam; Granger, Pascal; Pham-Huu, Cuong
Abstract: Hierarchical structure characterized by the decoration of few-layer graphene (FLG) surface with a dense network of carbon nanofibers (CNF) was synthesized by Chemical Vapor Deposition. This hierarchical composite was further used as host matrix for the dispersion of nanodiamonds (ND) to produce a metal-free catalyst for the direct dehydrogenation (DH) process of ethylbenzene (EB) to styrene. The as-synthesized three-dimension ND/CNF-FLG composite displays excellent dehydrogenation activity and stability, especially under severe reaction conditions similar to those in the industrial process. Up to 600 °C with EB concentration of 10 vol.%, the ND/CNF-FLG catalyst displays a significant high DH activity of 56 . 9 mmol ST g ND − 1 h − 1 along with 91.3% styrene selectivity. In addition, no deactivation is observed during more than 70 h of test. The outstanding catalytic performance and the superior stability of the hybrid ND/CNF-FLG composite compared to the conventional carbon-based and promoted iron industrial catalysts, render it among the most promising metal-free catalyst for industrial direct dehydrogenation process. Graphical abstract: The hierarchical carbon nanofibers/graphene supported nanodiamonds (ND/CNF-FLG) composite exhibits excellent catalytic activity and stability as metal-free catalyst for the steam-free direct dehydrogenation of ethylbenzene into styrene.